Hydrogen sulfide splitting using solar energy and hematite photo-anodes. (10th September 2019) - Bedoya-Lora, Franky E.; Hankin, Anna; Kelsall, Geoff H.
Abstract: The mechanism was investigated of hydrogen sulfide splitting in alkaline aqueous solutions using spray-pyrolysed Sn IV -doped α-Fe2 O3 photo-anodes in a photo-electrochemical cell. In principle, hydrogen sulfide splitting can be used to treat hydrogen sulfide in natural and process gases and simultaneously to produce hydrogen using solar energy. A comparison with conventional water splitting demonstrated the lower energy requirements to achieve the same photocurrent densities, while producing soluble polysulfide ions and elemental sulfur from hydrogen sulfide oxidation. However, neither splitting process was spontaneous using Sn IV -doped α-Fe2 O3 photo-anodes without inputs of electrical energy; two judiciously chosen photo-electrodes are required to achieve that objective. The effects were also studied of stirring, hydrogen sulfide ion concentration, electrode potential and annealing of Sn IV -doped α-Fe2 O3 films on titanium substrates. Under potentiostatic conditions during photo-assisted electrolysis, the photo-anodes exhibited no compositional or morphological changes after 18 h. In a bench-scale reactor (0.1 dm 3 ), stable photocurrent densities of ca. 12.5 A m −2 were recorded over 12 h at an electrode potential of 1.17 V vs . RHE and an effective irradiance of 2670 W m −2 . Similarly, photocurrent densities corresponding to ca. 4.3 A m −2 were achieved in an up-scaled reactor under an effective irradiance of 457 W m −2 . Charge yields for formation of polysulfide ions were close to unity when operating at optimised potentials and hydrogen sulfide ion concentrations. The shift towards lower electrode potentials of photocurrent densities for hydrogen sulfide splitting compared with those for water splitting was associated with increased charge transfer rates due to decreased interfacial electron-hole recombination rates. The potential dependences of sulfur coverage and oxygen evolution rates were also estimated.